Project Based Learning Implementation to Student's Scientific Attitude and Creativity Improvement - Aep Saepudin (Universitas Wiralodra, 2020)
ABSTRACT Scientific attitude and creativity of students in processing information when the learning process is still low. The purpose of this study is 1) to obtain data on the implementation of project based learning model learning can improve scientific attitudes, 2) to determine the implementation of project based learning model learning can increase student creativity. The method used in this research is the experimental method with the technique of sampling by cluster random sampling. The research instrument used was the task and rubric of students' scientific attitudes and creativity. Data analysis techniques normality, homogeneity and hypothesis. The hypothesis t=4.476 means that the implementation of the project based learning model of learning can improve scientific attitudes. The hypothesis t=8.486 means that the project based learning model of learning can increase student creativity. The conclusion is the implementation of the project based learning model of learning can improve students' scientific attitudes and creativity. Teachers should apply a project based learning model with video media on waste recycling materials.